REGULASI ZAKAT DI INDONESIA; UPAYA MENUJU PENGELOLAAN ZAKAT YANG PROFESIONAL - Muhammad Aziz (LPPM Institut Agama Islam Al-Hikmah Tuban, 2014)
In early Islamic history is described for government involvement in managing charity, with a model that is hardly the same, all of them can be said to be aimed at the welfare of the people. How does it happen in the context of the management of zakat in Indonesia! with a Muslim majority, is actually a good zakat management, will be able to prosper its people. This paper wants to answer two questions, namely; how the history of the regulation of zakat in Indonesia? and secondly, why is this zakat regulations should be regulated in the by-laws and regulations in Indonesia? This study used a qualitative approach with descriptive-comparative study-analytical, describing the history of the regulatory management of zakat in Indonesia, compare historical expert opinion, and then analyze it critically. Results of this study concluded that, first; history of the regulation of zakat in Indonesia characterized by a long struggle, and the tug between the interest of political Islamists and Islamist cultural interests and even the interests of the colonial occupiers in an effort to regulate the management of zakat. Secondly, this charity Regulation should be regulated by the State, is in order to improve the effectiveness and efficiency of service delivery in the management of zakat; and enhance the benefits of charity for the public welfare and poverty reduction. Effective management of zakat in Indonesia that this compound, requires legal certainty and clarity of regulations that govern them.